Reframing disorder: gender, class, and the history of the resurfacing debate in nursing - Matthias, April D. (East Carolina University, 2011)
The nursing profession has sustained a state of disorder. The debate within the disorder historically exists in relationship to multiple educational pathways for entry into RN practice. Diploma, BSN, and ADN pathways still exist today as a means to enter into nursing practice through RN licensure. Historical research of the three pathway developments is significant and timely in that the evidence from the study helps to shed light on professional issues resurfacing in the "BSN in 10" proposals.  The purpose of this research is to understand the socio-cultural-political context surrounding the decisions to develop the diploma, BSN, and ADN educational pathways; the historical debate concerning the role and functions, educational pathway, and professional identity of the entry-level RN; and the relationship between the educational pathway developments and the resurfacing historical debate.  Historical case study research focused on three historical decision points for the educational pathway developments: Diploma-Bellevue Training School for Nurses in New York, 1873; BSN-University of Cincinnati School for Nursing and Health in Ohio, 1916; and ADN-Orange County Community College nursing program in Middletown, New York, 1952. Archival retrieval of primary documents for each case study was completed.  Each educational pathway development revealed divisions of gender and paternalistic control over nursing, divisions of class within nursing, and an undefined division of nursing labor. Prolonged paternalistic control rooted in divisions of gender, coupled with the divisions of class and unstructured divisions of labor within nursing, prevented full realization of a professional, collegiate education for entry into RN practice.   The historical debate continues as a distinct professional identity and role does not exist for the entry-level RN. Lack of clear differentiation of role and functions within nursing practice for each pathway nurse creates an education-practice disorder, sustains division within the profession of nursing, and permits continued paternalistic control over nursing. Facing the "BSN in 10" proposals, nursing must reach a decision regarding the needed division of labor within nursing for today's health care system. Nursing can resolve the historical debate by reframing Montag's practice model and delineating an educational preparation for each practice role.
Keywords: Nursing; History; History of education; BSN in 10; Entry into practice; Women's history; Nursing Theory; Education, Nursing, Associate; Education, Nursing, Baccalaureate; Education, Nursing, Diploma Programs; Nursing Education Research; Sex Factors; Role